2014
DOI: 10.1177/0042098014538679
|View full text |Cite
|
Sign up to set email alerts
|

Suburban ways of living and the geography of income: How homeownership, single-family dwellings and automobile use define the metropolitan social space

Abstract: Current research depicts suburbs as becoming more heterogeneous in terms of socio-economic status. Providing a novel analysis, this paper engages with that research by operationalising suburban ways of living (homeownership, single-family dwelling occupancy and automobile use) and relating them to the geography of income across 26 Canadian metropolitan areas. We find that suburban ways of living exist in new areas and remain associated with higher incomes even as older suburbs, as places, have become more dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 53 publications
(78 reference statements)
4
35
0
2
Order By: Relevance
“…Across North‐America, suburbs have been historically understood according to three specific characteristics: a series of low‐density, automobile‐dependent areas surrounding a city core (Moos & Mendez, ). Richard Harris () sees “density,” “newness,” and “peripheral location” as the three defining qualities of a suburb, whereas Anne Forsyth () considers the latter two—peripheral location and newness—as common key features.…”
Section: Defining Suburbs: Manifold Concepts and Theories For A Lexiconmentioning
confidence: 99%
See 1 more Smart Citation
“…Across North‐America, suburbs have been historically understood according to three specific characteristics: a series of low‐density, automobile‐dependent areas surrounding a city core (Moos & Mendez, ). Richard Harris () sees “density,” “newness,” and “peripheral location” as the three defining qualities of a suburb, whereas Anne Forsyth () considers the latter two—peripheral location and newness—as common key features.…”
Section: Defining Suburbs: Manifold Concepts and Theories For A Lexiconmentioning
confidence: 99%
“…Across North-America, suburbs have been historically understood according to three specific characteristics: a series of low-density, automobile-dependent areas surrounding a city core (Moos & Mendez, 2015). Richard Harris (2010) sees "density," "newness," and "peripheral location" as the three defining qualities of a suburb, whereas Anne Forsyth (2014) housing types (at a first glance, low single-family dwellings are certainly considered the most common); social segregation (mainly class or ethnic); and cultural formations (utopian traditional models versus dystopian naturedevouring sprawl).…”
Section: Defining Suburbs: Manifold Concepts and Theories For A Lexmentioning
confidence: 99%
“…Their continuing expansion will be interpreted as an expression and catalyst of ongoing processes of inner-city suburbanization. When speaking of suburbanization, I refer to "the process of spreading of suburban ways of living to new geographic areas" (Moos/Mendez 2015: 1865. It is thus asserted that in Germany, as in many other Western urban regions, suburbanism has not only made its mark on the outskirts of the cities but is increasingly conquering growing parts of the inner cities as well.…”
Section: Innere Suburbanisierung -Kein Widerspruch In Sich üBer Die mentioning
confidence: 99%
“…With regard to the confusing picture she paints, Forsyth claims that we must either abandon the term or use it with greater precision (Forsyth 2012: 278 f.). Similarly, other researchers "consider the term 'suburb' to be obsolete or simply inadequate due to its inability to capture the diversity of neighborhoods contained within suburbs" (Moos/ Mendez 2015: 1868cf. also Murphy 2007;Florida 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As Amin claims in respect of cities as a whole, '[they] are hardly discernible entities with distinct identities. They have become an endless inhabited sprawl without clear boundaries' (Amin, 2006), while a recent study of Canadian metropolitan areas by Moos and Mendez (2014) found that although there is a positive relationship between higher incomes and suburban ways of living, these suburban spaces are becoming more diverse. As Florida (2014) observes, 'Not only are cities looking more like suburbs, suburbs are looking more like cities'.…”
Section: Manifestations Of Fraying In South East Queenslandmentioning
confidence: 99%